Indebtedness and the road to monetary sovereignty following the international recognition of Montenegro in 1878 - Radoslav Raspopovic (Revista de História da Sociedade e da Cultura, 2021)
The paper is dedicated to furthering the research into different aspects of Montenegrin sovereign status gained the Congress of Berlin, with a focus on the country’s financial sovereignty. Becoming an independent state had great historical significance for Montenegro, marking the realisation of the centuries-old aspirations for liberation. Still, exercising sovereign power proved challenging for Montenegro as the country was still an underdeveloped, agrarian country with a high percentage of illiterate population, scarce human resources and modest economic opportunities. Aside from this, there were still many congressional restrictions to exercising the rights acquired by gaining access to the sea. The author seeks to determine the reasons for the high level of indebtedness, as well as the decisions made in trying to resolve the challenges in maintaining the country’s financial sovereignty. The author also touches upon the broader subject of the role of gold standard in international trade and argues to which extent Montenegro was able to adhere to this internationally accepted standard, having established its banking institutions and having introduced its own currency. Considering that this paper is a part of the scientific research work on the project ‘Montenegro on the political and cultural map of Europe’ (CLIO MAP), exhibiting the reasons for minting the first Montenegrin coin is but a way to examine a segment in exibiting the country’s sovereign status acquired at the Congress of Berlin.